2021
DOI: 10.1021/acs.macromol.1c01211
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Copolymerization Using Simple Fe(III) Complexes and Metal- and Halide-Free Organic Catalysts

Abstract: A comprehensive range of 14 synthetically simple, air-stable, and structurally diverse Fe­(III) complexes, comprising salalen, salen, salan, and thiolen frameworks, were applied as catalysts to the ring-opening copolymerization (ROCOP) of phthalic anhydride (PA) and cyclohexene oxide (CHO) without the need for extra additives, such as co-catalysts, as part of a newly discovered unary system. Alternating poly­(1,2-cyclohexylene-1,2-phthalate) {poly­(CHO-co-PA)} was obtained with reasonable molecular weight, nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Additionally, the polymer molecular weights were much lower than expected for the single chloride initiator at short reaction times, which could be sensitivity to trace moisture in the epoxide. A prior study identified that protonated ligands were more active than the corresponding metal complexes with the ligands coordinated . A combination of the protonated ligand of 1 and [PPN]Cl showed similar side reactions to [PPN]Cl alone.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the polymer molecular weights were much lower than expected for the single chloride initiator at short reaction times, which could be sensitivity to trace moisture in the epoxide. A prior study identified that protonated ligands were more active than the corresponding metal complexes with the ligands coordinated . A combination of the protonated ligand of 1 and [PPN]Cl showed similar side reactions to [PPN]Cl alone.…”
Section: Resultsmentioning
confidence: 92%
“…A prior study identified that protonated ligands were more active than the corresponding metal complexes with the ligands coordinated. 33 A combination of the protonated ligand of 1 and [PPN]Cl showed similar side reactions to [PPN]Cl alone. However, the molecular weight of the polymer suggested the ligand as an initiating species for polymerization, since the molecular weight was less than half that for [PPN]Cl alone.…”
Section: The Presence Of [Ppn]mentioning
confidence: 90%
“…The MALDI-TOF MS of the obtained products confirmed the expected BDM-initiated polyethers structure and also revealed the presence of water-initiated species (Figures S14–S19). The water-initiated species was ascribed to the contamination of monomers with small amounts of water or monomer-derived glycol, the removal of which is very difficult and typically requires multiple distillations. , Notably, the carboxylate-initiated polymerization and chain transfer were suppressed in the ROP of all monomers, as evidenced by the related MALDI-TOF MS.…”
Section: Resultsmentioning
confidence: 99%
“…The water-initiated species was ascribed to the contamination of monomers with small amounts of water or monomer-derived glycol, the removal of which is very difficult and typically requires multiple distillations. 32,33 Notably, the carboxylate-initiated polymerization and chain transfer were suppressed in the ROP of all monomers, as evidenced by the related MALDI-TOF MS.…”
Section: ■ Experimental Sectionmentioning
confidence: 91%
“…[ 26–28 ] Especially iron complexes emerge as up‐and‐coming catalysts as a result of the relatively low toxicity and price of iron. [ 29–32 ] Mixed ligand complexes play a key role in biological chemistry because mixed chelation commonly occurs in biological fluids. [ 33–35 ] Synthesis and characterization of mixed ligand complexes are gaining importance day by day.…”
Section: Introductionmentioning
confidence: 99%